The Implementation of Contextual Teaching and Learning (CTL) Model in Improving the Learning Outcomes of Students in Ushul Fiqh Subject in Class 4H at Pondok Modern Darusaalam Gontor - Alfa Nisa Ilma Habibah; Iqramullah Iqramullah; Alfina Nur Asfika; Latifah Nisa Amini (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
As part of the learning resources, teachers bear the responsibility of creating a creative and enjoyable learning environment for students in the classroom, with the aim of stimulating their learning motivation. In this framework, the emphasized approach is the utilization of the Contextual Teaching and Learning (CTL) model, focusing on the full participation of students so that they can experience the learning process, connect it to real-world situations, and feel motivated. The expectation is that students can apply the acquired knowledge in their daily lives. This learning model encompasses a concept where teachers bring real-world situations into the classroom and encourage students to establish connections between the knowledge they acquire and its application in their daily lives. Therefore, the role of the teacher is to assist students in achieving their goals and engage more deeply with strategies rather than merely conveying information. One of the common issues faced by students in class 4H during Ushul Fiqh learning is a lack of concentration during the teaching process in the classroom. This can occur when the classroom environment lacks support, both in terms of cleanliness and comfort. Peer competition in the class, the physical structure of the classroom, both inside and during direct interactions with students, can also be contributing factors. In addressing these conditions, this research aims to find solutions to achieve the desired educational goals. The study employs a classroom action research methodology to enhance students' learning engagement and academic outcomes.